Literasi Keuangan dan Profesi Aktuaris di Sekolah Kota/Kabupaten Mojokerto - Zatadini, R. A. Diva; Permata, Reny Amalia; Oktaviarina, Affiati; Sofro, A’yunin; Maulana, Dimas Avian; Ariyanto, Danang; Khumairo, Nabilatul; Nofriyadi, Rizki (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2025)
The development of the financial industry requires human resources with adequate financial literacy and risk management understanding. However, teachers and students in Mojokerto still face challenges in the form of low financial literacy, particularly in personal financial management, long-term financial planning, and understanding risk concepts, as well as limited awareness of the actuarial profession as a strategic career path in the financial sector. This community service program aims to enhance the financial literacy of teachers and students through interactive and educational approaches, focusing on the introduction of basic financial literacy concepts and the actuarial profession as a strategic career opportunity in the financial industry. The activities include interactive seminars, case studies, simulations, and discussion sessions to strengthen participants’ comprehension. The program is expected to improve participants’ knowledge and skills in financial literacy, broaden their understanding of the actuarial profession. Based on the results of the pre-test and post-test, it can be concluded that the learning activities conducted had a positive impact on increasing participants’ knowledge, as evidenced by the rise in their average scores from 70.89 in the pre-test to 96.44 in the post-test. Overall, this program contributes to building financially literate school communities and preparing younger generations to face future economic challenges more effectively.